15th Annual Congress of the European Society for Photodynamic Therapy in Barcelona, Spain, February 12–13th 2016. Issue 3 (September 2016) - Braathen, Lasse; Morton, Colin; Szeimies, Rolf-Markus
Abstract We provide a summary of the presentations made at the recent Euro-PDT annual Congress. Presentations covered developments in topical photodynamic therapy (PDT) pertaining to dermatological applications. Recognizing the high prevalence and chronicity of actinic keratosis, one of the approved indications for PDT, there were recommendations to pursue field therapy to treat clinical and preclinical lesions. A separate section was reserved to review the strong evidence for the use of daylight PDT for actinic keratosis and experience of use of this well tolerated form of PDT was reported from several countries. Several presentations covered the remaining approved uses of topical PDT, Bowen's disease and basal cell carcinomas, as well as considering its role in so far unapproved indications including photorejuvenation. Funding: Galderma.